Prognostic Significance of Various Clinicopathologic Parameters and BRAF V600E Mutation in Papillary Thyroid Microcarcinoma—An Observational Study - Ayesha, Sobiya Mahnaz; Hui, Monalisa; Uppin, Shantveer G; Uppin, Megha Shantveer; Jena, Shubhranshu; Patil, Rajsekhar Shanthappa; Ratnagiri, Ranganath; Paul, Tara Roshni (Indian Journal of Medical and Paediatric Oncology, 2023)
Introduction A specific subset of papillary microcarcinoma of thyroid (PMC) can metastasize regionally and to distant organs, and thus, have a significant effect on the overall survival of the patient cohort.Objectives We aim to analyze the prognostic significance of various clinicopathologic parameters including BRAFV600E mutation by immunohistochemistry in PMC, in order to identify the subset of cases with aggressive behavior.Materials and Methods Data regarding the PMC cases was retrieved retrospectively from medical records. The clinicopathologic factors like age, tumor size, focality, capsular invasion, histologic subtype, lymphovascular invasion, perithyroidal fat invasion (PTFI), lymph node (LN) metastasis, and distant metastasis were studied in depth. Tissue microarray was constructed to perform immunohistochemistry with CK19 and BRAFV600E. Information regarding overall survival (OS) and development of metastasis, if any, was noted. Chi-squared test was performed to know the association between various factors. To determine odds ratio, logistic regression was done. Survival analysis was done using Kaplan–Meier and Cox-regression analysis.Results PMC was diagnosed in 48 patients (M:F = 1:2.4), between 22 and 70 years of age (median = 46.5 years). Chi-squared test showed significant association of fibrosis with tumor size more than or equal to 0.5 cm, infiltrative borders, PTFI, and LN metastasis. Tumor size was also associated with infiltrative borders; and LN metastasis with PTFI. BRAFV600E positivity showed significant association with histologic pattern, PTFI and distant metastasis. On logistic regression, tumor size showed significantly increased odds ratio with presence of fibrosis and infiltrative borders. Presence of fibrosis also showed significant association with infiltrative borders and LN metastasis. BRAFV600E had significantly increased odds ratio with histologic pattern, both on univariate and multivariate logistic regression. Kaplan–Meier analysis revealed significantly reduced OS with presence of LN metastases (p-value = 0.050, log-rank test). Cox-regression did not yield a significant hazard ratio for the various factors studied.Conclusion This study shows association of LN metastasis with intratumoral fibrosis, PTFI and reduced OS. Intratumoral fibrosis was also associated with tumor size more than 5mm, infiltrative borders and PTFI. Increasing tumor size and infiltrative borders also showed an association. In addition, BRAFV600E positivity was found to be associated with histologic pattern, PTFI and distant metastasis.
Keywords: thyroid; papillary microcarcinoma; prognosis; BRAFV600E; lymph node metastasis